ANALISIS KUALITATIF DAN KUANTITATIF MINYAK ATSIRI DAUN SIRIH HIJAU (Piper betle L.) DAN DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav.) BERASAL DARI KUPANG, NTT - Ayu Saraswati; Sajekti Palupi; Nikmatul Ikhrom Eka J. (CALYPTRA, 2018)
Abstract - This study aims to analyze qualitatively and quantitatively essential oils on green betel leaf (Piper betle L.) and red betel leaf (Piper crocatum Ruiz & Pav.) Taken from Kupang City, NTT. Qualitative test results of volatile oil of green betel leaf include liquid form, aromatic odor, brownish yellow color, bitter spicy taste, weight of type 0,7455 ± 0,013, and refractive index 1,46595 ± 0,019. Essential oils of red betel leaf include liquid form, aromatic odor, yellow color, bitter spicy taste, weight of type 0,7724 ± 0,001, and refractive index 1,46789 ± 0,009. Thin Layer Chromatography (TLC) stains on the volatile oil of green betel leaf showed 8 stains and the red betel leaves showed 9 stains. Analysis of Gas Chromatography-Mass Spectrometry (GC-MS) showed that on the volatile oil of green betel leaves there were 35 compounds with % quality> 90%, and dominated by 5 components of compounds with the largest area of Sabinene (6.72%), α -Copaene (6.23%), L-Calamenene (1.60%), trans-Caryophyllene (0.77%) and Cavicol (0.65%). Essential oil of red betel leaf 35 compound with% quality> 90%, and dominated by 5 component of compound with the largest area of β-Myrcene(13,80%), Linalool L (3,29%), α-Thujene (1 , 52%),γ- Terpinene (1.36%), cis-β-Terpineol (1.15%).